HUBUNGAN ANTARA SUPERVISI KEPALA SEKOLAH, BUDAYA KERJA, DAN MOTIVASI KERJA DENGAN KINERJA GURU SD SWASTA DI KECAMATAN MEDAN PETISAH KOTA MEDAN - Jasper Simanjuntak; Saut Purba; Artaida Sihite (FIP Unimed, 2021)
This study aimed to determine: (1) the relationship between the supervising principal with teacher performance; (2) the relationship between work culture with the performance of teachers; (3) the relationship between work motivation with teacher performance; and (4) the relationship between the supervision of the principal, work culture and work motivation with teacher performance. Subjects were private elementary school teachers in the district Medan Petisah, Medan City with a total sample of 122 people. Sampling was done by random sampling proportional. A descriptive research method that aims to obtain information about the symptoms in the study. Prior to this research, prior research instruments tested, followed by testing the validity and reliability testing. Questionnaire instrument valid teacher's performance earned 25 points out of 30 questionnaire items were tested, and has a reliability of 0.85. Questionnaire instrument supervision valid principals earned 26 points out of 30 questionnaire items were tested, and a reliability coefficient of 0.91. Questionnaire instrument valid work culture obtained 26 points out of 30 questionnaire items were tested, and a reliability coefficient of 0.88. Motivation questionnaire instrument obtained a valid work item 25 of the 30 items tested questionnaire, and a reliability coefficient of 0.89. Based on hypothesis testing can be concluded: (1) there is a significant relationship between the principal supervision of teacher performance ry1.23 = 0.36 > rtable = 0.17 and tcount = 6.12 > ttable = 1.65; (2) there is a significant relationship between teachers' work culture with the performance of ry2.13 = 0.21 > rtable = 0.17 and tcount = 2.88 > ttable = 1.65’; (3) there is a significant relationship between work motivation with teacher performance by ry3.12 = 0.30 > rtable = 0.17 and tcount = 4.59 > ttable = 1.65; and (4) there is a significant relationship between the principal supervision, cultural work, and motivation to work with teacher performance by Ry(123) = 0.50 > rtable= 0.17 and Fcount = 13.50 > Ftable = 2.65. The results obtained by the principal supervision, work culture, and motivation to work together to contribute 25% of the performance of teachers, and the rest are other circumstances determined